Water wise : native plants for intermountain landscapes - Mee, Wendy (Utah State University Press, 2003)
This comprehensive volume provides specific information about shrubs, trees, grasses, forbs, and cacti that are native to most U.S. states in the Intermountain West, and that can be used in landscaping to conserve water, reflect and preserve the region's landscape character, and help protect its ecological integrity. The book is an invaluable guide for the professional landscaper, horticulturist, and others in the Intermountain nursery industry, as well as for the student, general reader, gardener, and homeowner.